Pengembangan Video Pembelajaran sebagai Suplemen Bahan Ajar Tema 4 Kelas V SDN 03 Pontianak Kota - Megawati Megawati; Kartono Kartono; Suparjan Suparjan; Hery Kresnadi; Asmayani Salimi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to develop instructional video media as a complement to teaching materials on how to maintain the health of the human circulatory organs, Theme 4, Sub-theme 3, Learning 1. This type of research is development research using the ADDIE method. model (Analysis, Design, Development, Implementation, and Evaluation). Quantitative data in this study were obtained from product assessments by validation experts and also from the results of filling out questionnaires from the teacher and student respondents. Qualitative data were obtained from suggestions and notes by validators, teachers and students. The research instruments in this study were interview guidelines and questionnaires. The level of validity of learning video media as a complement to teaching materials is based on the results of media experts and material experts' assessments, while the level of product feasibility is assessed from responses to the use of instructional video media as a complement to teaching materials based on the assessment results of teachers and fifth grade students at SDN 03 Pontianak City. The validation results by media experts obtained an average value of 2.93 in the